Estimation of Tadalafil Using Derivative Spectrophotometry in Bulk Material and in Pharmaceutical Formulation. (21st May 2014) - Khan, Zamir G.; Patil, Amod S.; Shirkhedkar, Atul A.
Abstract : Four simple, rapid, accurate, precise, reliable, and economical UV-spectrophotometric methods have been proposed for the determination of tadalafil in bulk and in pharmaceutical formulation. "Method A" is first order derivative UV spectrophotometry using amplitude, "method B" is first order derivative UV spectrophotometry using area under curve technique, "method C" is second order derivative UV spectrophotometry using amplitude, and "method D" is second order derivative UV spectrophotometry using area under curve technique. The developed methods have shown best results in terms of linearity, accuracy, precision, and LOD and LOQ for bulk drug and marketed formulation as well. In N, N-dimethylformamide, tadalafil showed maximum absorbance at 284 nm. For "method A" amplitude was recorded at 297 nm while for "method B" area under curve was integrated in the wavelength range of 290.60–304.40 nm. For "method C" amplitude was measured at 284 nm while for "method D" area under curve was selected in the wavelength range of 280.80–286.20 nm. For methods A and B, tadalafil obeyed Lambert-Beer's law in the range of 05–50  μ g / mL while for "methods C and D", tadalafil obeyed Lambert-Beer's law in the range of 20–70  μ g / mL, and-for "methods A, B, C, and D" the correlation coefficients were found to be >  than 0.999.